Executive Function Profiles in Pediatric Traumatic Brain Injury. Issue 2 (17th February 2019) - Ringdahl, Erik N.; Becker, Megan L.; Hussey, Julia E.; Thaler, Nicholas S.; Vogel, Sally J.; Cross, Chad; Mayfield, Joan; Allen, Daniel N.
ABSTRACT: Traumatic brain injury (TBI) results in heterogeneous patterns of neuropsychological impairment. This study investigated heterogeneity in executive function (EF) using the Comprehensive Trail Making Test (CTMT) to evaluate 121 children and adolescents with TBI and 121 matched normal controls. The TBI group performed approximately two standard deviations below controls. Cluster analyses indicated that a three-cluster solution best classified the TBI group and a four-cluster solution best classified controls. Greater impairment in EF was associated with lower intellectual, achievement, and neuropsychological test performance in the TBI group. Results suggest that EF deficits reflected in CTMT performance may be useful for classifying severity of TBI.